2006
DOI: 10.1080/14765280600991917
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Provincial Productivity in China (1979–2001)

Abstract: This study analyzes provincial productivity growth in China for the period of 1979-2001. The Malmquist Index approach allows us to decompose productivity growth into two components, technical progress and efficiency change. Considerable productivity growth was found for most of the data period, but it was accomplished mainly through technical progress rather than efficiency improvement. Although China's capital stock has been accumulated at the speed of a historical record in recent years, our findings show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 29 publications
4
38
1
Order By: Relevance
“…Introducing new technologies there without first realizing the full potential of existing ones might be wasteful (Felipe, 1999). Several studies have found that TFP growth in China has been achieved more through technical progress than efficiency improvement (Zheng, Liu, and Bigsten 2003;Zheng and Hu, 2006). Since efficiency remains low, there are still large unexplored possibilities for efficiency-improvement in China.…”
Section: Technical Progress Vs Efficiency Improvementmentioning
confidence: 99%
See 2 more Smart Citations
“…Introducing new technologies there without first realizing the full potential of existing ones might be wasteful (Felipe, 1999). Several studies have found that TFP growth in China has been achieved more through technical progress than efficiency improvement (Zheng, Liu, and Bigsten 2003;Zheng and Hu, 2006). Since efficiency remains low, there are still large unexplored possibilities for efficiency-improvement in China.…”
Section: Technical Progress Vs Efficiency Improvementmentioning
confidence: 99%
“…Zheng and Hu (2006) (Economist, 2005). This was due to a decline in the growth rate of total factor productivity from 1993.…”
Section: China's Growth Pattern Since 1978mentioning
confidence: 99%
See 1 more Smart Citation
“…According to [3], the depreciation rate of 4 percent should be used in the calculation of capital stock. The output used is real gross regional product (GRP) (1995=100) and all the inputs and output vectors are value at RMB million.…”
Section: B Data and Definition Of Variablesmentioning
confidence: 99%
“…For example, one analysis (Hu et al 2008) uses DDF to rerank the technical change and efficiency of Chinese provinces once energy and emissions are taken into account, and shows different rankings compared to the more traditional measures (e.g. Zheng and Hu 2005). A 2010 study (Wang et al) estimates Chinese regional-level TFP and finds that changes in GTFP and TFP deviate from each other, with GTFP suffering mainly from the over-emission 3 See Wu (1995; Woo (1998) of sulphur dioxide and chemical oxygen demand.…”
Section: Introductionmentioning
confidence: 99%